Effective Communication and Transformational Leadership Influenced on Patient Safety Culture among Inpatient Nurses - Permatasari, Gilang; Indrawati, Ratna; Ramadhan, Yanuar (Alta Dharma Publisher, 2025)
Background: Patient Safety Culture plays an important role in reducing the incidence of accidents and injuries in the workplace, especially in hospitals. Objective: The study aimed to examine the effect of effective communication and motivation on patient safety culture with transformational leadership as an intervening variable on nurses in the inpatient room at Dr. Dradjat Prawiranegara Hospital. Method: A quantitative study with a cross-sectional approach was applied in this study for 83 nurses. The data was analyzed using the Structural Equation Model (SEM). Result: The result found that there is significantly affect between effective communication and motivation on patient safety culture with transformational leadership among nurses. Conclusion: The findings in this study indicated that effective communication on patient safety culture, and motivation on transformational leadership are the most dominant, and have a significant positive influence on transformational leadership in the inpatient room. Recommendation: It is recommended that hospital management strengthen effective communication systems among nurses and between nurses and leadership teams. For future research, longitudinal and experimental designs are recommended to examine the causal relationships between communication, motivation, and transformational leadership on patient safety culture over time